THE PROBLEM STUDY OF THE PROFESSIONAL TRAINING OF FUTURE SPECIALISTS IN PHYSICAL EDUCATION: A THEORETICAL ANALYSIS - Petrenko, N. (Continuing Professional Education: Theory and Practice, 2023)
The article deals with the main directions of training of future specialists in the field of physical education. The effectiveness of professional activities mostly determines the professional expertise of physical training and sport, which is a comprehensive personal human quality, which is under preparation, finally formed and developed in the course of practical activity and provides competent approach to solving professional tasks, conditions for improving educational activities. The mail aim of this article is touncover the main search domestic scholars and experts in the field of education regarding the study of professional training of future specialists in physical education. Professional training of future specialists in physical education and sport is a process that reflects the scientific and methodical and reasonable activities of higher education institutions, aiming at the formation during the period of study level of professional competence, personality, sufficient for the Organization of physical education of the various strata of the population in the region and successful work in all areas of sports movement taking into account modern requirements of the labor market. Effective training of future specialists in physical education and sport: a theoretically reasonable change of forms and methods of training in higher educational institutions, which should be aimed at the development of professional competence of the personality of the future specialist physical education and sport; in the process of physical education opportunities to explore different areas of activity of the future professionals of physical education and sports, the peculiarities of functioning of higher institutions in terms of socio-economic transformation of the society; psychological-pedagogical ensure conscious professional self-determination of personality of the future specialist physical education and sport opportunities for her professional self-actualization and professional self-realization.